Seasonal variation in stable carbon and nitrogen isotope values of bats reflect environmental baselines. - Ana G Popa-Lisseanu (PLoS ONE, 2015)
The stable carbon and nitrogen isotope composition of animal tissues is commonly used to trace wildlife diets and analyze food chains. Changes in an animal's isotopic values over time are generally assumed to indicate diet shifts or, less frequently, physiological changes. Although plant isotopic values are known to correlate with climatic seasonality, only a few studies restricted to aquatic environments have investigated whether temporal isotopic variation in consumers may also reflect environmental baselines through trophic propagation. We modeled the monthly variation in carbon and nitrogen isotope values in whole blood of four insectivorous bat species occupying different foraging niches in southern Spain. We found a common pattern of isotopic variation independent of feeding habits, with an overall change as large as or larger than one trophic step. Physiological changes related to reproduction or to fat deposition prior to hibernation had no effect on isotopic variation, but juvenile bats had higher δ13C and δ15N values than adults. Aridity was the factor that best explained isotopic variation: bat blood became enriched in both 13C and 15N after hotter and/or drier periods. Our study is the first to show that consumers in terrestrial ecosystems reflect seasonal environmental dynamics in their isotope values. We highlight the danger of misinterpreting stable isotope data when not accounting for seasonal isotopic baselines in food web studies. Understanding how environmental seasonality is integrated in animals' isotope values will be crucial for developing reliable methods to use stable isotopes as dietary tracers.